The Effectiveness of Using Questions Technique to Improve Students’ Writing of Recount Text - Maria Osmunda Eawea Monny (CV Wahana Publikasi, 2022)
Writing as a productive skill is considered a difficult skill to be mastered because not every student has better English proficiency which somehow has become an obstacle for them to construct better grammatical text. This research aims to improve the writing skills of recount text of students of Class CA of STMIK STIKOM Indonesia. The approach of this research is Class Action Research (CAR). The data collected are observation, interviews literary research, and tests. The results of this research showed that the implementation of Questions Guiding Techniques (QFT) was conducted successfully which can be seen through the results of cycle I and the progress made by students in cycle II. The results of cycle I (pre-test) and cycle II (post-test) were examined using an assessment rubric of writing text skills of recount text which consists of 5 aspects those are content, organization, structure, vocabulary, and mechanics with the score 4-3-2-1 (best-better-poor-poorer). The results of the cycle I (4-1) are 17-19-32-52. The result of cycle II shows that there is improvement in students understanding of grammar and writing skill on the recount text because score 4-3 is increased (36 – 95) and 2-1 is decreased (86 – 25) which shows better writing skills of the students.